Wadi Shuʿaib, Jordanien. Das Wadi Shuʿaib Archaeological Survey Project – Archäologische Forschungen zwischen Jordantal und transjordanischem Hochland. Die Arbeiten des Jahres 2017 - Ahrens, Alexander (e-Forschungsberichte des DAI, 2018)
The Wadi Shuʿaib Archaeological Survey Project (WSAS) was initiated in 2016. During the fall of 2017, the project’s second survey campaign was conducted in the region of the Wadi Shuʿaib, stretching from the town of as-Salt in the northwest to the Jordan Valley (Shuna South) in the southwest of Central Jordan. In the course of the second survey campaign, thirteen archaeological sites were recorded, raising the overall number of sites surveyed to 27. Additionally, small scale targeted excavations were conducted for the first time at the site of Tell Bleibil (Tall Bulaybil) located close to the alluvial fan of the Wadi Shuʿaib in the eastern part of the Jordan Valley in order to retrieve botanical samples for further analysis, including radiocarbon dating.